Dopamine Transporter Imaging for Frontotemporal Lobar Degeneration With Motor Neuron Disease - Kobayashi, Ryota; Kawakatsu, Shinobu; Ohba, Makoto; Morioka, Daichi; Kanoto, Masafumi; Otani, Koichi (Frontiers in Neuroscience, 2022)
Introduction Frontotemporal lobar degeneration (FTLD) is a clinical syndrome with pathological heterogeneity, including Pick’s disease and trans-activating response region (TAR) DNA-binding protein with a molecular mass of 43 kDa (TDP-43) proteinopathy (FTLD-TDP). A previous study reported abnormal findings on dopamine transporter (DAT) imaging in 30% of patients with frontotemporal dementia (FTD) in FTLD. However, the previous study did not consider the pathological heterogeneity of FTD regarding the pathomechanism leading to abnormal DAT findings. Recently, abnormal DAT findings were reported in two patients with FTLD with motor neuron disease (MND), of which FTLD-TDP type B was the most common pathological presentation. This study investigated the DAT findings of patients with a final diagnosis of FTLD-MND to determine the frequency of occurrence of DAT abnormalities in FTLD-MND. Methods Twenty patients with FTLD who underwent DAT single photon emission computed tomography (DAT-SPECT) were screened, and six patients with a final diagnosis of FTLD-MND were ultimately included. The patients’ DAT-SPECT findings were analyzed visually and quantitatively. Neuronal loss and astrogliosis in brain regions (substantia nigra, caudate, and putamen) that could possibly affect DAT findings were evaluated in the three pathologically confirmed cases. Result All six patients with FTLD-MND showed abnormal visual DAT-SPECT findings. In addition, in a quantitative assessment, the specific binding ratio in the striatum calculated by the Southampton method were below the lower limit of the 95% prediction interval of the healthy controls by age in all the present cases. Interestingly, three of the six patients showed abnormal findings on DAT-SPECT more than half a year before the onset of MND. Neuronal loss and astrogliosis in brain regions that may affect DAT findings were observed in three pathologically confirmed cases. Conclusion DAT-SPECT revealed abnormal findings in patients with FTLD-MND, which may manifest even before the onset of MND symptoms. We opine that the possibility of future development of MND should be considered if DAT-SPECT shows abnormal findings in FTLD.